PENGARUH PEMBERIAN PUPUK CAIR BIO URINE SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max L.) - Murdaningsih Murdaningsih; Marsianus Nate Ugha (Agriculture Faculty of Flores University, 2012)
This research aims to know the effect as well as the optimum rates of manure of urine cow bio to the growth and yield of the soybean plant. The design used in this study was Randomized Block Design and the treatment used is U0 (without bio urine manure), U1 (1375 litres of bio urine manure ha-1 or 550 ml plots-1), U2 (bio urine manure of 2750 litre ha-1 or 1100ml plots -1), U3 (bio urine manure 4125 litre ha-1 or 1650 ml plot-1), and U4 (bio urine manure of 5500 litre ha-1 or 2200 ml plot-1). Variable observation in this study is the height of the plant 33.8 cm, leaf number 2.90 strands, leaf area 1.17cm2, the weight of fresh residues tan-114,74 gr, dry oven weight of residue tan-1 15.50 gr, dry oven weight of residue ha-1 15.50kg, the number of pods 9.44 soybean, weight of 100 grain of soybean 1 0.91 gr, the weight of the seed tan-110.30 gr, seed dry weight ha-110, 30 kg, harvest index of 4.88 and optimum dosage of the manure of urine cow bio is 5500 litres ha-1 can increase the growth and yield of soybeans.